MHD casson fluid with radiative heat and mass transfer past an impulsively moving inclined plate - H. I., Osman; Zulkhibri, Ismail; Rozaimi, Abu Samah; Vieru, D. (WSEAS, 2023)
This paper explores the flow of Casson fluid that passes a moving inclined plate with the influence of double diffusions and radiation, where the fluid is imposed electrically conductive and moves through a porous medium. Several suitable non-dimensional variables are suggested in the model using partial differential equations with initial and boundary conditions. The corresponding non-dimensional governing equations are solved with the help of Laplace transform method. Analytical solutions to momentum, energy, and concentration are obtained, and the expression is in exponential and complementary error functions of Gauss. Finding solutions is limited to similar solutions for previous studies on Casson and viscous fluids as a special case. Computations are performed, where the outcomes are examined for embedded flow parameters.